Dietary management of heart failure: room for improvement?. Issue 7 (9th February 2016) - Butler, Thomas
Abstract: There is growing awareness of the role of diet in both health and disease management. Much data are available on the cardioprotective diet in the primary and secondary prevention of CVD. However, there is limited information on the role of diet in the management of heart failure (HF). Animal models of HF have provided interesting insight and potential mechanisms by which dietary manipulation may improve cardiac performance and delay the progression of the disease, and small-scale human studies have highlighted beneficial diet patterns. The aim of this review is to summarise the current data available on the role of diet in the management of human HF and to demonstrate that dietary manipulation needs to progress further than the simple recommendation of salt and fluid restriction.